1977
DOI: 10.1148/124.2.359
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography of the Kidney

Abstract: Computed tomography is an extremely accurate method of obtaining more definitive diagnostic information about a renal mass discovered on a urogram. Benign renal cysts are readily distinguished from solid renal neoplasms, and CT is often valuable in characterizing possible juxtarenal masses. The cause of a nonfunctioning kidney(s) on a urogram can often be discerned, and hydronephrosis is easily detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

1981
1981
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…Our study correlates with studies of Sagel et al [5] (1977), Bajwaet al [48] (2007), King [9] (1972) and Dachille et al [53] (2005) that demonstrated similar values as in present study for the detection of renal masses on USG and CT as shown Table 22 and Table 23. [53] (2005) 80 95…”
Section: Discussion:-supporting
confidence: 92%
See 1 more Smart Citation
“…Our study correlates with studies of Sagel et al [5] (1977), Bajwaet al [48] (2007), King [9] (1972) and Dachille et al [53] (2005) that demonstrated similar values as in present study for the detection of renal masses on USG and CT as shown Table 22 and Table 23. [53] (2005) 80 95…”
Section: Discussion:-supporting
confidence: 92%
“…Its non-invasive nature and extremely high diagnostic yield ultimately makes it an integral component of uroradiological diagnosis. [5] It is more accurate in delineating a renal mass and in differentiating between a pseudomass and a normal anatomic variant from a tumour and allows studies in patients who have dense renal calcification or in whom USG is technically difficult. It should be used in many areas for definite evaluation of lesions suspected from other studies, for example IVU or USG.…”
Section: Introduction:-mentioning
confidence: 99%
“…To determine the cause of the hematuria, the patient was assessed. The preferred diagnostic modality is the ultrasound since there is no risk of radiation to the developing fetus (9). Ultrasound findings showed an isoechoic to mildly echogenic well-marginated mass measuring 39 × 33 mm in the upper portion of the right kidney; the mass caused a bulge on the renal capsule of the upper pole of the right kidney.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a small cortical cyst with high echogenic content measuring 4 mm in the mid portion of the left kidney. The downside of ultrasound modality is that it is operator-dependent; therefore, full classification and the diagnosis of the renal mass would be suboptimal (9). Radiological contrast agents should be avoided because of teratogenicity effects and transplacental risk for the fetus (13).…”
Section: Discussionmentioning
confidence: 99%
“…10 CT has proved to be an extremely accurate method of differentiating a renal cyst from a neoplasm based on (a) attenuation value of the mass and whether it increased on giving intravenous contrast (b) demarcation of the mass from the normal renal parenchyma and (c) the thickness of the wall of the mass. 11 CT had become an essential imaging tool for the evaluation of the kidney and perirenal space as…”
Section: Introductionmentioning
confidence: 99%